Pengaruh Non Performing Loan dan Loan to Deposit Ratio terhadap Return on Asset - Muhammad Rafly Awaluddin; Haliah Haliah; Andi Kusumawati (CV. AFDIFAL MAJU BERKAH, 2023)
Banking is a financial sector institution that has a very important role in the financial system in Indonesia. As an intermediation institution, banks must have good performance, because by having good performance banks will be easier to gain the trust of customers. This study aims to determine how the effect of Non Performing Loan and Loan to Deposit Ratio on Return on Assets. This research was conducted on banking companies listed on the Indonesia Stock Exchange (IDX) using the financial statements of banking companies for 2017-2022. The population in this study is all banking companies listed on the Indonesia Stock Exchange as many as 44 companies. Sampling using the purposive sampling method so that companies that meet the criteria are 5 companies. This study uses multiple linear analysis and F test to find out how the influence between variables. The results of this study show that Non Performing Loan and Loan to Deposit Ratio simultaneously both have a significant effect on return on assets with a significance value of 0.000 < 0.05 in banking companies listed on the Indonesia Stock Exchange (IDX). However, partially non-performing loans have an effect on return on assets with a significance value of 0.000 < 0.05, while the loan to deposit ratio has no effect on return on assets with a significance value of 0.827 > 0.05 for banking companies listed on the Indonesia Stock Exchange (IDX).